Pengaruh Profitabilitas Dan Price Earning Ratio Terhadap Kebijakan Dividen - Khairul Anwar Pulungan (Lembaga Riset Ilmiah, Yayasan Mentari Meraki Asa, 2022)
This study aims to determine the effect of Profitability (ROA) and Price earning ratio (PER) partially and simultaneously on Dividend Policy. Profitability (ROA) and Price earning ratio (PER) are used as independent variables. Dividend Policy as the dependent variable. the research approach uses associative, the population in this study is 63 companies in the Basic Industry and Chemical sectors listed on the Indonesia Stock Exchange in 2015 - 2018. The sample is 8 companies multiplied by 4 years of research. The sample selection method is purposive sampling. The analytical method used to test the hypothesis is by using multiple linear regression analysis. The multiple linear regression analysis test is carried out on the first hypothesis that the Profitability variable (ROA) has no effect on Dividend Policy, the second hypothesis is that the Price earning ratio (PER) variable has no significant effect on Policy Dividend, in the third hypothesis which shows that Profitability (ROA) and Price Earning Ratio (PER) simultaneously have no effect on Dividend Policy.